Studies in the history of philosophy at the National University of «Kyiv-Mohyla Academy»: current methodological issues - Menzhulin, Vadym (Actual Problems of Mind, 2017)
By analysing the periodical publications of the Kyiv-Mohyla Academy’s Department of Philosophy and Religion the author presents an overview of certain methodological problems of the history of philosophy addressed and resolved by the members of this research and educational institution.